PERFORMANCE MEASUREMENT MANAGEMENT (PMM) IN THE DIGITAL ECONOMY: THE INSIGHTS FROM LITERATURE - Laily Abd Rahman; Siti Nabiha Abdul Khalid (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Rapid technological development, including the digitalisation of the industry, is changing the operations and management of businesses. Hence, businesses are facing challenges in ensuring that their Performance Measurement Management (PMM) system is contemporary and dynamic whilst dealing with constant change and rapid developments. Along with having to manage huge volume of data of different variability and the emergence of social media, keeping PMM current in today’s business setting has proved to be demanding. Therefore, the aim of this paper was to investigate how digitally-driven changes are impacting the management of PMM. A review of literature was conducted to understand how PMM and its elements are transformed by these economy landscape changes in an effort to provide insights for a state-of-the-art PMM system.